Uncertainty-driven business cycles: assessing the markup channel - Benjamin Born; Johannes Pfeifer (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2016)
A growing recent literature relies on a precautionary pricing motive embedded in representative agent DSGE models with sticky prices and wages to generate negative output effects of uncertainty shocks. We assess whether this model channel is consistent with the data. We build a New Keynesian DSGE model with time-varying wage and price markups and document the predicted conditional comovement of output and markups following demand and supply uncertainty shocks. Using the model as a business cycle accounting device, we also construct aggregate markup series from the data. Time-series techniques are used to identify uncertainty shocks in the data and to study whether the conditional comovement between markups and output is consistent with the one implied by the model. The response to uncertainty shocks is found to be consistent with precautionary wage setting, but not price setting, putting the role of sticky wages into the focus.
Keywords: E32; E01; E24; 330